2016
DOI: 10.1016/j.bbamem.2016.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Transport of haloacids across biological membranes

Abstract: Haloacids are considered to be environmental pollutants, but some of them have also been tested in clinical research. The way that haloacids are transported across biological membranes is important for both biodegradation and drug delivery purposes. In this review, we will first summarize putative haloacids transporters and the information about haloacids transport when studying carboxylates transporters. We will then introduce MCT1 and SLC5A8, which are respective transporter for antitumor agent 3-bromopyruvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 138 publications
0
9
0
Order By: Relevance
“…In our study, BPA lethal capacity was shown to be related to the levels of MCT1 expression (Figure 3A, 3C and 6A and Table 3 ). MCT1 was described as a BPA effective transporter in other studies [ 57 , 58 ] and MCT1 and other MCTs have been considered suitable vehicles for drug delivery [ 9 , 59 , 60 ]. Comparing to HL60 and THP1, HEL cells had a lower fold change in relative cell death induced by BPA both in the presence and absence of VEGF (Figure 6B ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, BPA lethal capacity was shown to be related to the levels of MCT1 expression (Figure 3A, 3C and 6A and Table 3 ). MCT1 was described as a BPA effective transporter in other studies [ 57 , 58 ] and MCT1 and other MCTs have been considered suitable vehicles for drug delivery [ 9 , 59 , 60 ]. Comparing to HL60 and THP1, HEL cells had a lower fold change in relative cell death induced by BPA both in the presence and absence of VEGF (Figure 6B ).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of α‐halogen substituents to a C=O bond finely modulates the reactivity profile, thus making the resulting scaffolds valuable entities . In this scenario, α‐halo carboxylic derivatives occupy a prominent position also in view of their relevance in biology and agrochemistry . The Hell‐Volhard‐Zelinsky (HVZ) reaction represented the classical approach to these compounds (Scheme a): the treatment of a carboxylic acid with elemental halogen in the presence of a quasi‐stoichiometric phosphorous catalyst at high temperatures furnishes the targeted adducts.…”
Section: Methodsmentioning
confidence: 99%
“…[1] In this scenario, a-halo carboxylic derivatives occupy a prominent position also in view of their relevance in biology [2] and agrochemistry. [1] In this scenario, a-halo carboxylic derivatives occupy a prominent position also in view of their relevance in biology [2] and agrochemistry.…”
mentioning
confidence: 99%
See 2 more Smart Citations